2000
DOI: 10.1007/s004410000277
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of testican expression in human brain

Abstract: Testican is a putative extracellular heparan/ chondroitin sulfate proteoglycan of unknown function that is expressed in a variety of human tissues at widely different levels but is most abundant in the brain. In mice, testican mRNA has been detected only in brain and it is therefore likely to have an important function in the central nervous system. RNA blot analysis reveals the relative intensity of testican in various regions of the human brain. Levels of testican message are most pronounced in the thalamus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…1A, inset, arrows) and choroid plexus (Fig. 1A, white arrows), which is consistent with the previous report (13). On the other hand, testican-1 mRNA increased mainly in the margin surrounding the necrotic region of the cortex at day 7 after cryo-injury (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…1A, inset, arrows) and choroid plexus (Fig. 1A, white arrows), which is consistent with the previous report (13). On the other hand, testican-1 mRNA increased mainly in the margin surrounding the necrotic region of the cortex at day 7 after cryo-injury (Fig.…”
Section: Resultssupporting
confidence: 91%
“…3), suggesting that both molecules are expressed in reactive astrocytes. Previous study has shown that in Northern blot analysis of various mouse tissues testican-1 mRNA expression is restricted to the brain (13). In situ hybridization histochemistry reveals that testican-1 mRNA is expressed in pyramidal neurons of the hippocampus.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Members of this family are upregulated during seizures and long-term potentiation (Kato et al, 1997). Clone 280244 (Class 1b) is 54% similar to testican, a putative extracellular heparan/ chondroitin sulfate proteoglycan expressed in a variety of human tissues but is most abundant in brain (Marr et al, 2000). Using subtractive hybridization, Genini et al (1996) identified testican as highly down-regulated in an embryonal-rhabdomyosarcoma cell line as compared to human primary myobasts.…”
Section: Genetic Analysismentioning
confidence: 99%